Profits and margins along Uganda's charcoal value chain - Shively, G.E.; Jagger, P.; Sserunkuuma, D.; Arinaitwe, A.; Chibwana, C. (2010)
This paper characterizes the charcoal value chain in Uganda, focusing on production and trade in three districts in the west central region of the country. Data come from surveys of 407 charcoal value chain participants undertaken in 2008. The surveys included 171 charcoal-producing households and 236 non-producer participants including agents, traders, transporters and retailers. Linear regression models are used to study overall profits and per-unit marketing margins along the value chain and to test several hypotheses regarding the importance of location, human and social capital, and asset ownership on observed economic returns and scale of activity. Evidence suggests the greatest overall returns to participation in the charcoal value chain are found among traders. Returns are positively correlated with the scale of activity. Controlling for a participant's role in the charcoal trade, his or her characteristics, and available assets, we find little or no evidence of differences in economic returns among districts, despite widespread popular views of differences in available supply of charcoal. Location of production relative to major markets, and location-specific levels of monitoring and enforcement are not strongly correlated with observed outcomes.